Analisis Kemampuan Literasi Media Pada Mahasiswa dalam Mencegah Tindak Kriminalitas (Studi Kasus Pada Komunitas Immedia ) - Pratama, Sapta Wahyu; Pane, Endi Hadian Sabar; Sazali, Hasan; Andinata, Maulana (Peneliti.net, 2023)
As time goes by, we cannot deny that technological developments cannot be avoided anymore. Technological developments clearly make it easier for humans to communicate and reach information with a wide range. The transition of mechanical and analog technology to digital technology is a sign that we are in the digital era, this technological change then causes changes in human culture. One example of these changes can be seen in the way people think and act in everyday life. However, in line with the development of media technology, new criminal acts have emerged. This crime occurs on social media, for that we are required to have good media literacy skills in order to avoid and prevent criminal acts that might occur. Therefore, this study aims to analyze the media literacy abilities of students who are members of the Immedia community as an effort to prevent crime. For data validity, interviews were conducted with students in the Immedia community. The results of this study indicate that the level of student media literacy is practically very good and continues to increase.